Digital Reconstruction and Preservation of North Sumatra’s Cultural Heritage: Integrating Generative Adversarial Networks (GAN) and Augmented Reality (AR) for Enhanced Historical Site Visualization - Systematic Literature Review - Eka, Muhammad; Saari, Erni Marlina (International Journal of Advances in Data and Information Systems, 2026)
The integration of Generative Adversarial Networks (GAN) and Augmented Reality (AR) in cultural heritage preservation offers significant potential to enhance educational engagement and tourism experiences. GAN provides high-fidelity digital reconstructions of historical sites, while AR adds immersive, interactive elements that bring these reconstructions to life, fostering a deeper connection with cultural narratives. However, challenges such as data quality, technical constraints, and the need for user-friendly design must be addressed to fully realize the benefits of these technologies. These challenges are particularly prominent in remote or resource-limited areas, where infrastructure may be inadequate. To maximize the potential of GAN and AR, future research should focus on improving dataset quality, enhancing GAN algorithms, and developing accessible, scalable AR applications that prioritize ease of use. By addressing these challenges, GAN and AR can become transformative tools for preserving cultural heritage and fostering greater public engagement, ensuring that cultural treasures are both protected and made accessible for future generations.